Cultivating commoners: Infrastructures and subjectivities for a postcapitalist counter-city - Dombroski K; Conradson D; Diprose G; Healy S; Yates A (Elsevier B.V., 2023)
In this paper, we investigate how infrastructure and care shape commoner subjectivities. In our research into an urban youth farm in Aotearoa New Zealand, we heard and observed profound tales of growth and transformation among youth participants. Not only were our interviewees narrating stories of individual transformation (of themselves and others), but they also spoke of transformations in the way they engaged with the world around them, including the land and garden and its many species and ecological systems, the food system more generally, the wider community and their co-workers. Such transformations were both individual and collective, having more in common with the collective caring subject homines curans than the autonomous, rational work-ready subject of homo economicus. Using postcapitalist theory on commons, commoning and subjectivity, we argue that these socio-affective encounters with more-than-human commons enabled collective, caring commoner subjectivities to emerge and to be cultivated through collective care in place. We suggest that the commons can be thought of as an infrastructure of care for the counter-city, providing the conditions for the emergence and cultivation of collective caring urban subjects.